PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILATAS DAN PERTUMBUHAN SEBAGAI PEMODERASI (Studi Empiris pada Peusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode Tahun 2018-2020) - Siti Nur Azrina; Junaidi Junaidi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The research objective is to analyze the effect of capital structure on firm value, capital structure effect on profitability, capital structure effect on growth and capital structure affect on firm value with profitability and growth as moderating. This type of research is explanatory research, because this research aims to test a theory. The population used in this study is the annual report of manufacturing companies registered in Indonesia for 2018-2020. Data analysis technique using moderated regression analysis (MRA) is an analytical approach that maintains sample integrity and provides a basis for controlling the influence of moderator variables. The conclusions of the research results can be described as follows: there is a significant influence between capital structure on firm value, capital structure has a significant influence on profitability, there is a significant influence between capital structure on growth and profitability to be a moderating variable of the effect of capital structure on company value. Indonesia stock exchange. As for the growth variable, it does not moderate the effect of capital structure on firm value.Keywords: Capital Structure, Firm Value, Profitability and Growth